STRES KERJA PADA KARYAWAN YANG BERKAITAN DENGAN FAKTOR PSIKOSOSIAL LINGKUNGAN KERJA - Albasithu, Farras Fahira; Wartono, Magdalena (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
Every company demands good productivity from its employees. However, there are things that can cause a decrease in work productivity, one of which is work stress. This common mental state in employees can be caused by bad work environment psychosocial factors. Decreased of work productivity could occur because employees who experience stress would find it difficult to concentrate and easily tired. This research was conducted to determine the relationship between psychosocial factors in the work environment and work stress on employees. Method: Observational research with a cross-sectional study using the COPSOQ-II and SDS questionnaires on 112 employees at ministry in 2021. Data analysis used the Chi-Square test and was processed using the SPSS program with a significance level used of 0.005. Results:The results of the analysis between the psychosocial factors of the work environment and work stress on employees obtained a value of p = 0.000 which indicated that there was a significant relationship (p <0.005). So it could be concluded that there was a significant relationship between psychosocial factors in the work environment and work stress on employees. Conclusion: This study shows that there is a significant relationship between psychosocial factors in the work environment and work stress on employees.